Performance analysis of location update in LTE based network / Noor Elfi Aziani Noor Azmi - Noor Azmi, Noor Elfi Aziani (2013)
A tremendous demand on mobile wireless technology due to the ability in providing users with information on the move has pushed development of mobile communication. Heterogeneous network architecture has attracted attention to boost performance and requirement of coverage in the most cost effective way. However, a massive volume of data to be processed and tunneled through network increased signaling traffic and long signaling delay. The aim of this project is to reduce signaling cost incurred in cellular network. Two schemes, centralized location management and distributed location management are proposed in handling a cost efficient signaling traffic. A simulation algorithm is developed using MATLAB software to evaluate signaling cost. The simulation is carried out using different parameters which are number of UEs at one time within network and network size. The result shows that, distributed location management has better performance in reducing signaling cost when number of UEs and network size increased.